The Effect of Mixing Method on Preparing Chitosan-Zeolite-Fe Composites on Fe(III) Release - Ratu Fazlia Inda Rahmayani; Yateman Arryanto; Indriana Kartini (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Preparation of an Fe(III) slow-release materials using chitosan and zeolite and evaluation of their release behavior in the 0.33 M citric acid has been done. The composite synthesis was carried out by varying the method of mixing basic ingredients. The first method was done by mixing chitosan gel, zeolite and Fe solution altogether (composite A). The second method was done by mixing chitosan gel with Fe solution and stirring, after that adding zeolite (composite B). The last method was done by interacting zeolite with Fe solution then stirring and then adding chitosan gel (composite C). The structure of the composite was characterized using an infrared spectrophotometer (FTIR), X-Ray diffractometer (XRD), and SEM. Evaluation of release in the citric acid 0.33 M for composite showed that the order of release of Fe(III) from the fastest was chitosan-Fe, composite A, composite B, composite C, zeolite-Fe with values of k are 0.049 mg/g; 0.016 mg/g; 0.015 mg/g; 0.011 mg/g; and 0.006 mg/g, respectively. The SEM images of composite showed rough surface morphology of composites due to the presence of zeolite-Fe which was not coated by the chitosan framework. Thus, it can be concluded that the chitosan-zeolite-Fe composite can be used as a Fe(III) slow-release composite but the variation of mixing method of the materials does no effect on the Fe(III) slow-release properties.